2012
DOI: 10.1108/00220411211209186
|View full text |Cite
|
Sign up to set email alerts
|

Legitimising bibliotherapy: evidence‐based discourses in healthcare

Abstract: Legitimising bibliotherapy: from problematisation to irreversibility? PurposeTo explore how a self-help bibliotherapy scheme became national policy, focusing on its legitimisation via policy agendas and institutional discourses.Design/methodology/approach A mixed methodological approach was used to gather data, incorporating semi-structured interviews, documents and descriptive statistics. Actor-Network Theory (ANT) was used as a critical lens to frame analysis. FindingsThe study concludes that that while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…Looking at the contribution of the library service in isolation may 98 PMM 16,1 not be helpful for long range strategic planning. Brewster et al (2012) demonstrate how different stakeholders in a bibliotherapy, books on prescription, scheme had different viewpoints on why and how the scheme should operate, and how the benefits, or value, could be achieved. An actor-network theory approach helped to understand how working arrangements and roles were negotiated, and the value of the bibliotherapy service made, as far as possible, legitimate.…”
Section: Value Constellationmentioning
confidence: 99%
“…Looking at the contribution of the library service in isolation may 98 PMM 16,1 not be helpful for long range strategic planning. Brewster et al (2012) demonstrate how different stakeholders in a bibliotherapy, books on prescription, scheme had different viewpoints on why and how the scheme should operate, and how the benefits, or value, could be achieved. An actor-network theory approach helped to understand how working arrangements and roles were negotiated, and the value of the bibliotherapy service made, as far as possible, legitimate.…”
Section: Value Constellationmentioning
confidence: 99%
“…At some point, some bibliotherapeutic practice in the VAHLS moved from reading for general edification to reading reliable literature about the patient's condi tion. In 1959, Morrow and Kinney reported that VAHLS patients were reading "popular psychiatric and psychological articles and books" [9], Moreover, the practice of assigning poetry or fiction reading for self-help continues in some bibliotherapeutic models to this day [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Even so, there is a basis for its use, particularly among individuals who are good readers and are highly motivated to heal. However, this structure does not have the benefits of some of the later programs that ISSN 2380-9183 E-ISSN 2380-9205 use group participation to create a more flexible environment tailored to the needs of the users (Brewster, Sen, & Cox, 2012).…”
Section: Books On Prescriptionmentioning
confidence: 99%
“…This is due to government policy initiatives that focus on evidence-based practices (EBP) that can be used for a countrywide plan for bibliotherapy in public libraries. Researchers and policy makers have collected information that has been of use in creating a national project (Brewster, Sen & Cox, 2012).…”
Section: The Uk Modelmentioning
confidence: 99%
See 1 more Smart Citation